Analisis Spesifik Rasio Perbankan Indonesia terhadap Return on Asset dan Return on Equity. - Kristiana, Deranika Ratna (AKMENIKA, 2016)
This research is aimed to examine the influence of the banking specification ratio to the return on asset and the return on equity. The implication of this research is hoped to be able to give more understanding, especially for the emitter as the basic of the consideration in making decision to maximize the performance of the company and the shareholders. So, it has big return, for the investor in making the invested decision and for the banking customer in making the consideration in choosing the financial institution that will be become as the place to save the deposit or to propose the credit. The previous research is expected that the banking specification ratio gives the positive influence to the profitability. The test of the variables in this research will be done by entering the variables to a multiple analysis regression. The sample of this research is done to the national banking registered in the stock exchanges of Indonesia and that has the complete banking data in Indonesia from 2011 to 2015.